Unite Against Racism demonstration, 1994 (1994)
1994 1960-2000 "Unite Against Racism demonstration, 1994" [T0563.jpg], 1994 Following the election of a British National Party councillor in Millwall, East London and the escalation in racist attacks in the area, the TUC joined with a broad platform of anti-racist organisations in a Unite Against Racism demonstration in Tower Hamlets on 19 March, 1994. Some 50,000 people joined the demonstration. The BNP candidate was defeated in the subsequent local elections and a Labour Council returned to power in the borough.